The characteristics of imported cases and the effectiveness of outbreak control strategies of pandemic influenza A (H1N1) in China - Zhang, Yi; Yang, Peng; Liyanage, Surabhi; Seale, Holly; Deng, Ying; Pang, Xinghuo; Tian, Lili; Liu, Baiwei; Zhang, Li; Wang, Quanyi (Asia-Pacific journal of public health, 2012)
The aim of this article was to describe the epidemiological characteristics of imported cases of pandemic influenza A (H1N1) and to assess the effectiveness of public health intervention measures in Beijing, China. Data on imported cases were collected via border entry screening, influenza-like illness screening in hospitals, medical follow-up of travelers from overseas, and quarantined close contacts. The characteristics of these cases were investigated. Pharyngeal swabs were collected and tested using polymerase chain reaction. A total of 609 imported cases were confirmed in Beijing from May 16 to September 30, 2009. Subjects aged <20 years accounted for 47.3%, and females represented 49.1%. Most cases were from North America and South America (27.3%). There were 21.8%, 18.7%, 3.1%, and 56.3% of cases detected separately via border entry screening, quarantined close contacts, medical follow-up of travelers from overseas, and influenza-like illness screening in hospitals, respectively. The 4 strategies were able to detect the cases efficiently but the use of resources was high.